Periodic maintenance plan for the pavement in the busstop Las Retamas – Los Angeles bridge section - Ramirez Medina, Daniel Alexis (2023)
The general objective of this study was to design a periodic maintenance plan for Paradero Las Retamas - Puente Los Angeles section of the Central highway, developed in 2021. For this purpose, a quantitative, descriptive, non-experimental, cross-sectional approach methodology was applied to a sample population of 1,9 km distributed in 13 sampling units of 230,42 m2, to which the Pavement Condition Index (PCI) was determined according to its own methodology. A traffic study was also conducted to determine the composition and classification of vehicles, and the drainage system was inspectedto identify the current pavement conditions. In addition, physical properties were analysed through laboratory tests to determine the International Regularity Index (IRI) and the Present Serviceability Index (PSI), considering the stipulations ofthe Ministry of Transportation and Communications (MTC). Finally, the information was processed using HDM-4 software to determine the most appropriate periodic maintenance strategies. In this way, an overall PCI of 62 was obtained, qualified as “good”, and an Average Daily Annual Index (IMDA) of 31 236 vehicles/day, which classifies the road as a first-class highway. On the other hand, the most viable maintenance alternative was a simple surface treatment, accompanied by the uniform application of a layer of bituminous binder on the granular pavement, combined with an optimal routine maintenance. The evaluation criteria show the profitability of the project, showing a Net Present Value (NPV) of 3,20 million soles (844 804 USD) and an Internal Rate of Return (IRR) of 20 %. Finally, a positive impact on the PSI is obtained as a result of the implementation of the alternative.